2019
DOI: 10.3389/fpubh.2019.00231
|View full text |Cite
|
Sign up to set email alerts
|

Visitors to a Tropical Marine Beach Show Evidence of Immunoconversions to Multiple Waterborne Pathogens

Abstract: Determining infections from environmental exposures, particularly from waterborne pathogens is a challenging proposition. The study design must be rigorous and account for numerous factors including study population selection, sample collection, storage, and processing, as well as data processing and analysis. These challenges are magnified when it is suspected that individuals may potentially be infected by multiple pathogens at the same time. Previous work demonstrated the effectiveness of a salivary antibod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…This study followed a similar sampling protocol and analytical design to previously conducted studies. In brief, this study used a multiplex Luminex platform to detect salivary antibody responses to antigens (Ag) as shown in Table 1 [ 6 , 13 , 15 , 16 ]. Table 1 provides information on the organism, antigen, source of where the antigen was purchased/acquired, and the amount of antigen coupled to the beads.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study followed a similar sampling protocol and analytical design to previously conducted studies. In brief, this study used a multiplex Luminex platform to detect salivary antibody responses to antigens (Ag) as shown in Table 1 [ 6 , 13 , 15 , 16 ]. Table 1 provides information on the organism, antigen, source of where the antigen was purchased/acquired, and the amount of antigen coupled to the beads.…”
Section: Methodsmentioning
confidence: 99%
“…In previous work, we described the development and utility of salivary antibody multiplex immunoassays in measuring symptomatic and asymptomatic infections, immunoprevalence, coinfections and incident infections associated with recreating in contaminated waters and other environmental and water-related exposures [ 13 , 14 , 15 , 16 , 17 , 18 ]. These research efforts demonstrated that the immunoassays could provide cost and time savings in comparison to traditional enzyme-linked immunosorbent assays (ELISAs) as more analytes are added to the assay [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cutoff criteria were established in reference 32 [cutoff ϭ 10 mean (h) ϩ 3 SD (h) , where h ϭ log 10 (MFI of control beads)] to distinguish immunopositive and immunonegative samples and employed to measure immunopositivity and immunopreva- lence (baseline immunopositivity) in the population. Immunoconversions are defined using the more stringent three-sample criterion presented by Simmons et al (33), which extends the traditional 4-fold increase from S1 to S2 definition to ensure that the S2 sample is immunopositive (MFI Ն cutoff point) and accounts for the fact that IgG levels are expected to remain relatively high and not drop to zero during the 30-to 40-day period after initial exposure; accordingly, the immunoconversion criteria are S2 Ն 4 ϫ S1, S2 Ն cutoff, and S3 Ն 3 ϫ S1. Immunoconversions were computed only for study participants who provided all three samples.…”
Section: Methodsmentioning
confidence: 99%
“…Our team developed a bead-based, multiplex salivary antibody immunoassay to measure the prevalence of antibodies to multiple waterborne pathogens associated with drinking and recreational water contamination simultaneously (30,31). Application of the assay has allowed us to measure immunoprevalence (32), immunoconversions (incident infections), coinfections (33), and asymptomatic infections (34) from exposure to various waterborne pathogens in visitors to Boquerón Beach, Puerto Rico. Immunoprevalence (the prevalence of circulating antibodies against specific pathogens) is an important aspect of these studies because it affords the ability to capture the baseline level of exposure at the beginning of a longitudinal study.…”
mentioning
confidence: 99%
“…In 2016 WHO reported that globally some 12.6 million deaths each year can be ascribed to unhealthy environments. Moreover, 24% of global deaths (and 28% of deaths among children under five) come from modifiable environmental factors (Prüss-Ustün et al, 2016). Human epidemiological studies and experiments in laboratory animals proved that exposure to some pollutants can increase susceptibility to diseases such as diabetes, heart disease, and reproductive cancers.…”
Section: Introductionmentioning
confidence: 99%